2018
DOI: 10.1021/acsphotonics.8b00327
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-Enhanced Single-Molecule Enzymology

Abstract: We present a numerical study on plasmon-enhanced single-molecule enzymology. We combine Brownian dynamics and electromagnetic simulations to calculate the enhancement of fluorescence signals of fluorogenic substrate converted by an enzyme conjugated to a plasmonic particle. We simulate the Brownian motion of a fluorescent product away from the active site of the enzyme, and calculate the photon detection rate taking into account modifications of the excitation and emission processes by coupling to the plasmon.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As an example, the 1/ e decay length of field intensity is about 5 nm for a gold nanorod with a diameter of 30 nm. 46…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, the 1/ e decay length of field intensity is about 5 nm for a gold nanorod with a diameter of 30 nm. 46…”
Section: Resultsmentioning
confidence: 99%
“…25,45 However, maintaining colloidal stability requires long PEG linkers to prevent aggregation during centrifugation or at physiological salt conditions, pushing the conjugated biomolecules away from the particle’s surface where the refractive index sensitivity and fluorescence enhancements are highest. 15,46 Although it has been observed that histidine-tagged biomolecules can effectively conjugate to inorganic quantum dots with zero-length spacing, 47 no general protocols exist that allow for the conjugation of a range of proteins to different types of plasmonic nanoparticles using short linkers while simultaneously preserving protein activity and colloidal stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,45 However, maintaining colloidal stability requires long PEG linkers to prevent aggregation during centrifugation or at physiological salt conditions, pushing the conjugated biomolecules away from the particle's surface where the refractive index sensitivity and fluorescence enhancements are highest. 15,46 Although it has been observed that histidine-tagged biomolecules can effectively conjugate to inorganic quantum dots with zerolength spacing, 47 no general protocols exist that allow for the conjugation of a range of proteins to different types of plasmonic nanoparticles using short linkers while simultaneously preserving protein activity and colloidal stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plasmonic nanoapertures have shown great potential in optical sensing, spectroscopy, imaging, , nanofabrication, , trapping, and nonlinear photonics . With their capacities of localizing electromagnetic field to subdiffraction regions, reducing detection volume to attoliters, and enabling background-free optical detection, nanoapertures are particularly attractive for scientific studies at the single-molecule level. For example, their use in performing fluorescence correlation spectroscopy has enabled single-analyte characterization at high micromolar concentrations. , As optical nanotweezing elements, the nanoapertures have been used for sensing or analyzing various nanoparticles such as quantum dots, , proteins, , and DNA , with single-molecule resolution.…”
mentioning
confidence: 99%